UJI LINEARITAS BERDASARKAN ESTIMASI MEAN DAN VARIANSI BERSYARAT UNTUK PROSES RUNTUN WAKTU - Supriyanto Supriyanto; Herni Utami (Jurusan Matematika FMIPA Universitas Jenderal Soedirman, 2009)
This study aims to examine the benefits of testing linearity in the case of live test data. Bootstrap procedure is used to form the estimators of the statistics. Hypothetical form is used to follow the linear model. And compare the value of criticism from the distribution of this value with the test statistics that have been calculated based on the observed time series data existing. This procedure starts with a model determines autoregression to the data. By using the Akaike information criterion, order estimation obtained from the autoregression models.